ANALISIS FAKTOR PENGHAMBAT KETERAMPILAN MEMBACA PADA SISWA KELAS RENDAH DI MI UMDATUR RASIKHIEN JAKARTA - Atikah, Siti; Asiyah, Siti; Ningsih, Septi Setya; Malikah, Siti Afriatul; Fauziah, Sifa; Khoirunnisa, Siti (STAI Darul Qalam Tangerang, 2025)
This research was conducted at MI Umdatur Rasikhien Jakarta. The problems identified in this study are the inhibiting factors of reading skills in lower grade students. This study aims to describe: (1) To determine the reading skills of lower grade students at MI Umdatur Rasikhien Jakarta, (2) To determine the inhibiting factors of reading skills in lower grade students at MI Umdatur Rasikhien Jakarta, (3) To determine the methods used to improve reading skills in lower grade students at MI Umdatur Rasikhien Jakarta. This study uses a qualitative approach with a descriptive type of research. The subjects in this study were the principal, lower grade teachers, and lower grade students at MI Umdatur Rasikhien Jakarta. Data collection was carried out through observation, interviews and documentation. Data analysis used three stages consisting of data reduction, data presentation, and drawing conclusions. Data examination or checking was carried out by triangulation of data sources and triangulation of techniques. The results of the study showed that reading skills in lower grade students still have errors, namely: (1) Errors in recognizing letters, (2) Understanding vocabulary, (3) Difficulty in reading words or lip movements when reading, (4) Reading by spelling, (5) Understanding one letter at a time, (6) Reversing words and reading too fast so that words are overtaken when reading. The factors that influence reading skills in lower grade students include physiological, psychological, and environmental factors. The way to improve reading skills in lower grade students is to foster a love of reading by providing learning reading materials such as textbooks, reading texts, and getting used to reading regularly by giving students the opportunity to learn to move forward, teachers give students time to read one to three lines of reading, and use teaching aids to teach children who cannot or do not understand letters or reading.